EFEKTIVITAS APE KARTU KATA BERGAMBAR DALAM PENGEMBANGAN BAHASA ANAK USIA 5-6 TAHUN DI RA MIFTAHUL HUDA CEMORO - Muhammad Saufi; Riris Wahyuningsih; Jon Iskandar Bahari (Islamic EduKids: Jurnal Pendidikan Anak Usia Dini, 2022)
Language development in children is the ability to express language orally, both recognizing pictures, symbols of the letters of the alphabet, spelling and reading vocabulary as well as the ability to communicate. This study aims to describe the effectiveness of the picture word card educational game tool in language development for children aged 5-6 years at RA Miftahul Huda Cemoro. The place and time of this research was conducted on Jl. General Sudirman No. 02 Cemoro Hamlet, Balak Village, Songgon District, Banyuwangi Regency. This study uses qualitative descriptive research from data obtained through interviews, observation and documentation. The data analysis technique used the Miles and Huberman model. The stages in learning activities carried out through the application of pictorial word card educational game tools, namely the planning stage, the implementation stage and the evaluation stage. At the evaluation stage the teacher uses a checklist assessment. From the results of the final accumulation of assessments using 4 indicators that have been determined as a reference for assessment, there were 8 children who achieved BSB scores (developed very well) and 2 children achieved BSH scores (developed as expected). This shows that the application of picture word card educational games can stimulate the development of language skills in children optimally.